Perceptions and Key Factors Influencing the Concept of Smart Bangladesh - Talukdar, Md. Monowar Uddin; Alam, Khayrul; Ferdous, Shakila; Akter, Ripa (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study explores the concept of a smart Bangladesh, focusing on the roles of smart citizens, government, society, and economy. It argues that leveraging technology is not limited to digitizing government services but also involves transforming the interactions between citizens, society, the economy, and the government. The findings highlight the significant influence of smart citizens and a smart economy on this concept, emphasizing its relevance for both developing and underdeveloped countries. A total of 179 responses were collected using random sampling, ensuring comprehensive coverage for structured interviews based on the Likert scale. The impact was analyzed using inferential statistics with SmartPLS (Version: 4.0.9.9). Bibliographic data spanning from 2018 to 2023 were visualized using VOSViewer, mapping 214 pieces of literature from the Web of Science (WoS) database to support the concept. Structural Equation Modeling (SEM) and Exploratory Factor Analysis (EFA) yielded an R-square value of 51%. The results confirm the acceptance of hypotheses H1 (β = -0.057, t = 0.730, p > 0.233) and H4 (β = 0.603, t = 5.459, p < 0.000), showing a direct effect on the smart concept. This study presents a holistic approach to sustainable development through technological transformation, consolidating research across smart domains like healthcare, education, agriculture, payments, and grids.